The Batangan Exhibition Center and Hotel - Martin, Corenne G.; Litonjua, Emmanuel A. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The Batangan Exhibition Center and Hotel is a project that aimed to bring national and international conventions to Batangas City. The project, located strategically located near the Batangas Port and the STAR Tollway, shall spur the economic development in the city. It is a facility that responds to the different spatial needs of convention event organizers and attendees, adapts to the dynamics of business and trade, and lastly, it provides for the entrepreneurial needs of the users. Zoning, linkage and hierarchy are the design concepts incorporated in the design. The zoning and hierarchy of spaces according to their level of privacy, accessibility, and function is critical both in the exhibition center and the hotel as the flow of movement of the convention event organizers, attendees, and hotel guests and the back of the house employees must not interfere with each other. Linkage connects the exhibition center and the hotel as these two are entirely of different typology but have related functions in this context. Linkage was achieved by designing a connecting bridge, a pedestrian network, and a common loading bay.
Includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman